2017
DOI: 10.1002/cam4.1247
|View full text |Cite
|
Sign up to set email alerts
|

Toenail mineral concentration and risk of esophageal squamous cell carcinoma, results from the Golestan Cohort Study

Abstract: Studies conducted in China linked selenium deficiency to higher risk of esophageal squamous cell carcinoma (ESCC), but this has not been widely tested outside that selenium‐deficient region. The aim of this study was to investigate the association between selenium and other mineral concentrations in toenails and risk of ESCC in a region with high incidence rates. In this nested case–control study, we identified 222 cases of ESCC from the Golestan Cohort Study, Iran, which has followed up 50,045 participants si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(52 reference statements)
0
10
1
Order By: Relevance
“…With respect to generalizability, it is important to consider how mercury exposures in the present study compare with those in prior studies and with average population exposures. Toenail Hg concentrations were substantially lower in the present study population when compared to those reported in several other US-based 18,4042 studies, and studies outside the US 35,4347 , several of which involved toenail measurements performed in the same laboratory as in the present study 35,42,45 . The primary source of MeHg exposure in humans is the dietary consumption of fish, with highest concentrations found in longer-lived, larger fish that bioaccumulate MeHg 8,9,48 .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…With respect to generalizability, it is important to consider how mercury exposures in the present study compare with those in prior studies and with average population exposures. Toenail Hg concentrations were substantially lower in the present study population when compared to those reported in several other US-based 18,4042 studies, and studies outside the US 35,4347 , several of which involved toenail measurements performed in the same laboratory as in the present study 35,42,45 . The primary source of MeHg exposure in humans is the dietary consumption of fish, with highest concentrations found in longer-lived, larger fish that bioaccumulate MeHg 8,9,48 .…”
Section: Discussioncontrasting
confidence: 73%
“…To the best of our knowledge, this is the first population study to examine MeHg as a risk factor for glioma and is unique in cancer studies by examining both a biomarker of exposure (toenail Hg) and polymorphic variation in MeHg metabolism 35 . Crespo-Lopez et al .…”
Section: Discussionmentioning
confidence: 99%
“…People in high risk populations have often consumed a restricted diet, low in fruit, vegetables, and animal products, so deficiencies of micronutrients have been postulated to explain the high risk (boxes 1 and 2). Despite several observational studies and some randomised trials, however, the relative roles of various micronutrients are not yet clear 17181920. In Western countries early case-control studies indicated a protective role for fruit and vegetables,2122 but more recently published prospective studies show weaker associations, which might be due to residual confounding from smoking and alcohol consumption 16…”
Section: Oesophageal Cancermentioning
confidence: 99%
“…Cohort studies in the Netherlands revealed an inverse association between selenium level in the toenail and risk of ESSC (107). However, a case-control study in the Golestan Province did not find such correlation (108). In a Chinese population, low dietary selenium intake was found as a major risk factor for ESSC (109), especially in smokers and heavy drinkers with p53 Pro/Pro and GSTP1 Ile/Ile genotypes (110).…”
Section: Selenium and Antioxidant Defense Systemsmentioning
confidence: 84%